Genomic diversity and evolution analysis of severe fever with thrombocytopenia syndrome in East Asia from 2010 to 2022 - Wang, Yao; Pang, Bo; Wang, Zequn; Tian, Xueying; Xu, Xiaoying; Chong, Xiaowen; Liang, Hao; Ma, Wei; Kou, Zengqiang; Wen, Hongling (Frontiers in Microbiology, 2023)
Background: Conducting an up-to-date analysis on the genomic diversity and evolution patterns of severe fever with thrombocytopenia syndrome virus (SFTSV) is crucial for elucidating the underlying mechanisms of its emergency and pathogenicity, as well as assessing the extent of its threat to public health. Methods: Complete genome sequences of SFTSV were obtained from GenBank until December 19, 2022. A thorough phylogenetic analysis was conducted using comprehensive bioinformatics methods to estimate the genomic diversity and evolution. Results: The phylogenetic classification of SFTSV strains yielded seven lineages (A-G) for each genome segment. SFTSV displayed notable variations in evolutionary patterns among different regions and segments, without a linear accumulation of nucleotide substitutions within segments and regions. The comprehensive analysis revealed 54 recombination events and 17 reassortment strains, including the first discovery of recombination events involving sea-crossing and species-crossing. Selection analysis identified three positive sites (2, 671, 1353) in RNA-dependent RNA polymerase, three positive sites (22, 298, 404) in glycoprotein, and two positive sites (9, 289) in nonstructural protein. No positive selection sites were found in nucleoprotein. Conclusions: Our study unveiled the existence of multiple evolutionary forces influencing SFTSV, contributing to its increasing genetic diversity, which had the potential to modify its antigenicity and pathogenicity. Furthermore, our study highlights the importance of tracking the spread of SFTSV across regions and species.